The trained nurse - Patten, Ethel Faye (My University, 1895)
Introduction: “I have long been of the opinion that there should be in all the principal towns and cities of this Union, institutions for the education of men and women whose duty it is to take care of the sick and to carry out the injunctions of the medical attendant. Millions of human beings perish annually in this so-called civilized world for want of good nursing.” So spoke Dr. Gross, his opinion having been formed, not hastily, but after years of careful experience. This is the universal opinion of the medical world of today; but back in the second century, where first we hear of hospitals, no such thing as nursing was known. Under the pall of mythology and superstition, where all disease was but the wrath of the gods, serious sickness nearly always meant death. The first account we have of nurses is during the Crusades, when Guy of Montpelier, France, established a hospital for nursing and aiding the poor. We cannot rightly call this a training school, except as they were trained by experience—doubtless our modern schools would look at the effort in disdain—yet it may be marked as the first recorded effort in that direction for humanity.
Citation: Patten, Ethel Faye. The trained nurse. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Nursing; Medicine; Training; Theses; Manuscripts (documents)